9p-13q+12p+19q=

Simple and best practice solution for 9p-13q+12p+19q= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9p-13q+12p+19q= equation:


Simplifying
9p + -13q + 12p + 19q = 0

Reorder the terms:
9p + 12p + -13q + 19q = 0

Combine like terms: 9p + 12p = 21p
21p + -13q + 19q = 0

Combine like terms: -13q + 19q = 6q
21p + 6q = 0

Solving
21p + 6q = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-6q' to each side of the equation.
21p + 6q + -6q = 0 + -6q

Combine like terms: 6q + -6q = 0
21p + 0 = 0 + -6q
21p = 0 + -6q
Remove the zero:
21p = -6q

Divide each side by '21'.
p = -0.2857142857q

Simplifying
p = -0.2857142857q

See similar equations:

| x+119+x+59=180 | | 15=-3n-3 | | 20+(2)(6)= | | 13f+7g+3f+4g= | | -3(x-1)+2=4 | | X-3x-9+2=21 | | 2y+2=-5+10y | | 8s+4r+13s+6r= | | V=x(24-2x)(24-2x) | | 2y+7-4y=-17 | | x^2+10x-200= | | 9+3*x=-6 | | 75x=2100 | | -5+24x=23x | | 10c+9v+6c-7v= | | 32=18-2k | | -191=-7-8(-5+4a) | | 5+24x=23x | | 5+24x=23 | | 3.1r=13.95 | | 7a+10b+6a-3b= | | -5+24x=23 | | 4=n+10 | | x+3=68 | | 7j+4j= | | 5x^4=5x | | 4f-8=-4n-12 | | 8+4(-8+3)=-12 | | 6+(n+7)2=25 | | (4x-16)=(2x+6) | | -6x=114 | | -4x-12y=12 |

Equations solver categories